PERAN ORANG TUA DALAM MEMBENTUK KARAKTER ANAK USIA DINI MELALUI POLA ASUH DALAM KELUARGA DI TK ASYIFA - Rohayu Fadilla; Anggun Dwi Putri; Mutia Khoirunnisya Nasution; Dinda Okta Olipia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explore how parents contribute to developing the character of early childhood children through parenting approaches applied within the household. Character formation during the golden age becomes the initial foundation that will continue to influence the child's personality development into adulthood. This research uses a library research method by reviewing a number of related scientific sources, published between 2022 and 2026. The findings of the study show that the democratic parenting style is the most successful approach in fostering positive character in early childhood, such as independence, responsibility, honesty, and empathy toward others. Parents who practice democratic parenting give children space to express themselves while consistently instilling moral values.